Levantamento e observações naturalísticas da acarofauna (Acari, Arachnida) de seringueiras cultivadas (Hevea spp., Euphorbiaceae) no Brasil - Feres, Reinaldo J.F [UNESP] (Sociedade Brasileira de Zoologia, 2000)
This paper reports twenty eight acarine species belonging to twenty four genera in eleven families, associated with rubber trees, Hevea spp. (Euphorbiaceae), from Brazil. A key to the genera and species is included.
Survey and naturalistic remarks on the acarological fauna (Acari, Arachnida) from Hevea spp. (Euphorbiaceae) in Brazil
Keywords: Acari; Mites; naturalistic remarks; Hevea; Rubber tree; Brazil